Exploring the 13CO/C18O abundance ratio towards Galactic young stellar objects and H II regions - Areal, María Belén (2018)
Aims. Determining molecular abundance ratios is important not only for the study of Galactic chemistry, but also because they are useful to estimate physical parameters in a large variety of interstellar medium environments. One of the most important molecules for tracing the molecular gas in the interstellar medium is CO, and the 13CO/C18O abundance ratio is usually used to estimate molecular masses and densities of regions with moderate to high densities. Nowadays isotope ratios are in general indirectly derived from elemental abundances ratios. We present the first 13CO/C18O abundance ratio study performed from CO isotope observations towards a large sample of Galactic sources of different natures at different locations. Methods. To study the 13CO/C18O abundance ratio, we used 12CO J = 3 - 2 data obtained from the CO High-Resolution Survey, 13CO and C18O J = 3 - 2 data from the 13CO/C18O (J = 3 - 2) Heterodyne Inner Milky Way Plane Survey, and some complementary data extracted from the James Clerk Maxwell Telescope database. We analyzed a sample of 198 sources composed of young stellar objects (YSOs), and HII and diffuse HII regions as catalogued in the Red MSX Source Survey in 27°.5 < l < 46°; .5 and /b/ < 0° .5. Results. Most of the analyzed sources are located in the galactocentric distance range 4.0-6.5 kpc. We found that YSOs have, on average, lower 13CO/C18O abundance ratios than HII and diffuse HII regions. Taking into account that the gas associated with YSOs should be less affected by the radiation than in the case of the others sources, selective far-UV photodissociation of C18O is confirmed. The 13CO/C18O abundance ratios obtained in this work are systematically lower than those predicted from the known elemental abundance relations. These results will be useful in future studies of molecular gas related to YSOs and HII regions based on the observation of these isotopes.